2023
DOI: 10.1111/bcpt.13839
|View full text |Cite
|
Sign up to set email alerts
|

Betaine—The dark knight of the brain

Abstract: The role of betaine in the liver and kidney has been well documented, even from the cellular and molecular point of view. Despite literature reporting positive effects of betaine supplementation in Alzheimer's, Parkinson's and schizophrenia, the role and function of betaine in the brain are little studied and reviewed. Beneficial effects of betaine in neurodegeneration, excitatory and inhibitory imbalance and against oxidative stress in the central nervous system (CNS) have been collected and analysed to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 106 publications
1
14
0
Order By: Relevance
“…In the past few decades, several studies have reported the beneficial effects of betaine in neurological and neurodegenerative diseases. Its systematic supplementation showed only mild side effects [4, 45, 46], making it a therapeutic molecule of interest. However, the presence of betaine in the brain and the mechanism involved leading to its positive action still remained a puzzle, deeming it a “dark knight” [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, several studies have reported the beneficial effects of betaine in neurological and neurodegenerative diseases. Its systematic supplementation showed only mild side effects [4, 45, 46], making it a therapeutic molecule of interest. However, the presence of betaine in the brain and the mechanism involved leading to its positive action still remained a puzzle, deeming it a “dark knight” [4].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, betaine is mainly found in the liver, kidney, and brain. However, the presence and role of betaine in the brain is poorly understood and remains debated [4].…”
Section: Introductionmentioning
confidence: 99%
“…34 On the other side, many studies reported the neuroprotective effects of betaine. 32,35 In the current study, three behavioral tests were used to shed light on the locomotion and cognitive impairment caused by CuO-NP intoxication and the possible amelioration effect of betaine.…”
Section: Behavioral Assessmentsmentioning
confidence: 99%
“…The transport of betaine across membranes is facilitated, in part, by the betaine‐GABA transporter (BGT1), which is expressed in the liver, kidney and brain. In their review, Bhatt et al 14 address the scarcity of detailed molecular and cellular insights into betaine's actions in the brain.…”
mentioning
confidence: 99%